Assessment of consumer participation and behaviour towards the “No Plastic Bag Campaign” in Kuala Lumpur - Syed Ismail, Sharifah Norkhadijah; Suhaimi, Nur Syakirah Hanani; Karuppiah, Karmegam (Human Resource Management Academic Research Society, 2021)
This study assessed the consumer’s participation and behavior in the plastic bag campaign in the country. Participant observation and assessment were conducted among 396 shoppers at 3 different stores (i.e. hypermarket, supermarket, and convenience store) around Kuala Lumpur. Half of the shoppers in this study were observed purchased plastic bags (52%, n = 206) while shopping. They are mainly the supermarket (66.7%) and hypermarket visitors (54.5%). Meanwhile, 48% (n = 190) of shoppers did not purchase plastic bags and mainly the visitors of the convenience store (52.3%). Most of the male shoppers purchase plastic bags while shopping (55.2%, 96 out of 174). Only 49.5% of female shoppers (n = 110) purchase plastic bags. This study also highlights 63.9% of the consumers who shopped in a group usually pay for plastic bags. High participation was observed among visitors of the convenience store (N = 86, 65.2%) and those who shopped alone (N = 151, 52.4%). There is a significant association between shoppers' participation in the “no plastic bag campaign” with the type of retailers (X²=38.075, p=<0.001) and shopped alone (X²=0.177, p=<0.001). Participation in the campaign was not associated with gender, ethnicity, time, and week of shopping. In conclusion, the observation of consumer behaviors and participation in the plastic bag campaign was considered as low and need for further encouragement.